A CROSS LAYER INTERACTIVE PROTOCOL MECHANISM FOR MANET WITH A REALISTIC RESPONSE TO NETWORK STIMULATION - M Abdul Gafur; Niraj Upadhayaya; Syed Abdul Sattar (European Scientific Journal, ESJ, 2013)
Protocol layering technique employed in TCP/IP reference model limits interaction among the layers. Any alteration of a network element as a response to a network condition is made and used inside of its limited scope. Benefits of any protocol enhancement are not resulted in a significant overall performance of network. In this paper we bring an effective interaction among the protocol layers by sharing valuable state information. This information is used for making a correct decision for an optimized adaptation or reasonable response. In this paper we have brought some enhancement in Medium Access Control layer and network layer in such a way that network element in one layer is useful for the improvement of network element in other layer. In other words we have made a value addition for different network variables. Simulation result shows that our approach provides significant performance enhancement in Mobile adhoc networks in terms of various performance metrics like throughput, packet reception, delay etc.